Optimal Planning and Management of Hybrid Vehicles in Smart Grid - Mortazavi, Seyed Mohammad Bagher; Shiri, Nabiolah; Javadi, Mohammad Sadegh; Dehnavi, Saeed Daneshvar (Ciência e Natura, 2015)
Smart grid can be expressed as a combination of power network substructures with an extensive telecommunication network which is able to provide a two-way communication and use of advanced sensors in order improve efficiency, system reliability, transport security, and power consumption. Loads in this network are divided into two groups, linear and non-linear. The majority of these loads on the network, such as rectifiers, electric vehicles are non-linear. The non-linear loads can cause odd harmonics in the network and can damage transformers. In this article, management and planning of hybrid vehicles for total harmonic index reduction and also annual cost reduction has been considered.